Staphylococcus aureus Osteomyelitis: Bone, Bugs, and Surgery - Urish, Kenneth L; Cassat, James E (Infection and immunity, 2020)
Osteomyelitis, or inflammation of bone, is most commonly caused by invasion of bacterial pathogens into the skeleton. Bacterial osteomyelitis is notoriously difficult to treat, in part because of the widespread antimicrobial resistance in the preeminent etiologic agent, the Gram-positive bacterium Bacterial osteomyelitis triggers pathological bone remodeling, which in turn leads to sequestration of infectious foci from innate immune effectors and systemically delivered antimicrobials. Treatment of osteomyelitis therefore typically consists of long courses of antibiotics in conjunction with surgical debridement of necrotic infected tissues. Even with these extreme measures, many patients go on to develop chronic infection or sustain disease comorbidities. A better mechanistic understanding of how bacteria invade, survive within, and trigger pathological remodeling of bone could therefore lead to new therapies aimed at prevention or treatment of osteomyelitis as well as amelioration of disease morbidity. In this minireview, we highlight recent developments in our understanding of how pathogens invade and survive within bone, how bacterial infection or resulting innate immune responses trigger changes in bone remodeling, and how model systems can be leveraged to identify new therapeutic targets. We review the current state of osteomyelitis epidemiology, diagnostics, and therapeutic guidelines to help direct future research in bacterial pathogenesis.